The "Spacemaker", a New Device for Minimally Invasive Cardiothoracic Surgery: An Evaluation and Feasibility Study. Issue 4 (July 2015) - Lozekoot, Pieter W.J.; Gelsomino, Sandro; Kwant, Paul B.; Parise, Orlando; Matteucci, Francesco; de Jong, Monique M.J.; Maessen, Jos G.; Gründeman, Paul F.
Objective: Our aim was to evaluate a new inflatable lung retractor, the "Spacemaker", and its efficacy in facilitating minimally invasive cardiothoracic surgery without the need of one lung ventilation or carbon dioxide overpressure insufflation. Methods: The device was tested in 12 anesthetized pigs (90–100 kg) placed on standard endotracheal ventilation. The device was introduced into the right or left side of the chest, depending on the intended procedure to be performed, via a 3-cm incision in the fifth intercostal space. A total of seven animals were used to evaluate hemodynamic and respiratory response to the device, whereas another five animals were used to assess the feasibility of a variety of minimally invasive cardiothoracic surgical procedures. Results: Introduction was easy and unhindered. The device was inflated up to 0.6 bar, thereby pushing the lung tissue gently away cranially, posteriorly, and caudally without interfering with pulmonary function or resulting in respiratory compromise. In addition, hemodynamics remained stable throughout the experiments. Different closed-chest surgical procedures such as left atrial appendage exclusion, pulmonary vein exposure, pacemaker lead placement, and endoscopic stabilization for coronary surgery, were successfully performed. Removal was quick and complete in all cases, and lung tissue showed no remnant atelectasis. Conclusions: The "Spacemaker" may represent a reliable alternative to current conventional techniques to facilitate minimally invasive cardiothoracic surgery. Further research is warranted to confirm the effectiveness and the safety of this device and to optimize the model before its use in humans and its introduction into clinical practice.